Penerapan Parliamentary Threshold pada Pemilihan Umum 2009 - Itasari, Nur’Ayni (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
The selection process through theÂ (general) election mechanism can be identified with the electoral system ever implemented in the Islamic government. First, the electoral system of ahl al-hall wa al-'aqd which was carried out by the trust and allegiance. Second, the electoral system of ahl al-hall wa al-'aqd which was done through the periodic election, selection in society, and by the head of state. Parliamentary Threshold (PT) is a threshold mechanism in place at legislative elections (for parliament) with a percentage of 2.5% for the political parties which contested the election to follow the counting in the determination of the House of Representativeâ€™s seats. Parliamentary Threshold, according to Law No. 10 year 2008, article 202, paragraph 1 (regarding the election of members of DPR, DPD and DPRD) in the 2009 election, was implemented by calculating the minimum total of 2.5% of the valid votes in the national political party contestants. Then those parties were listed, which ones were the Parliamentary Threshold and which ones were not the Parliamentary Threshold to determine BPP to calculate the DPRâ€™s seats for the electoral partyÂ contestants that had passed the threshold.